Preparations Use Based on Bacteria of the Genus Bacillus to Increase the Yield of Oats (Avena sativa L.) - Andrei V. Platonov; Irina I. Rassokhina; Georgii Yu. Laptev; Vladislav N. Bolshakov (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The work studies the effect of microbiological preparations based on the culture of B. subtilis and B. megaterium on the growth processes, photosynthetic parameters, and grain productivity of oats. Field tests were conducted in 2019 in the conditions of a micro plot experiment in the North-West of Russia. Microbiological preparations were introduced by soaking seeds and treating plants in the third leaf stage with preparations of 1 ml/l.The research finds that the introduction of microbiological preparations leads to a significant increase in growth. In the tillering stage, the leaf surface area of the experimental plants was higher by up to 40.1%, and plants' fresh and dry mass increased by 27.8–58.9%. Introducing microbiological preparations increased the average daily increments and the net productivity of plant photosynthesis by 1.080–2.801 g/m2. By the time of harvesting, the mass of the experimental plants remained higher by 13.4–23.3%. The studied preparations increased the grain productivity of oats by up to 16.3% compared to the control. The study indicated a positive effect of microbiological preparations based on B. subtilis and B. megaterium strains on oats.